Analysis of Seismic Performance of Damaged Wooden Structure Column Foot. Issue 1 (September 2020) - Zhou, Xin; Li, Tieying; Wang, Yifan; Wang, Jianliang
Abstract: In order to study the dynamic response of the damaged timber frame column foot, a four-grade single-span timber frame model with damaged column foot was established to study the frequency change of the timber frame, and the acceleration trend of column top and foot under different frequencies and different peak harmonics were analyzed. The results show that the frequency range of the damaged wooden frame of the column foot is 0.8HZ-2.5HZ. With the increase of the input peak value, the shock absorption effect of the wooden frame under 100gal is obviously better than 50gal. As the elastic modulus of the damaged column foot increases, the shock absorption effect of the wooden frame gradually weakens.